Long-Term Safety and Efficacy of Tacrolimus 0.1% in Severe Pediatric Vernal Keratoconjunctivitis. Issue 11 (November 2021) - Caputo, Roberto; Marziali, Elisa; de Libero, Cinzia; Di Grande, Laura; Danti, Gioia; Virgili, Gianni; Villani, Edoardo; Mori, Francesca; Bacci, Giacomo M.; Lucenteforte, Ersilia; Pucci, Neri
Abstract : Purpose: The aim of this study was to evaluate the safety and efficacy of tacrolimus 0.1% eye drops in a large population of pediatric patients affected by a severe form of vernal keratoconjunctivitis (VKC) who responded poorly to cyclosporine eye drops. Methods: This is a retrospective study based on standardized clinical charts and data collection of consecutive patients affected by severe VKC who responded poorly to cyclosporine eye drops topical treatment but treated with tacrolimus 0.1% eye drops with a follow-up of 18 months. Four clinical signs were graded for analysis: hyperemia, tarsal papillae, giant papillae, and limbal papillae. The blood tests for kidney and liver function and the tacrolimus level were studied. Visits were scheduled at baseline and at 3, 6, 12, and 18 months. Patients received tacrolimus 0.1% eye drops in both eyes 2 times daily. Results: Four hundred thirty-one patients were included. Three hundred twenty-five patients were affected by a seasonal form, whereas the remaining 106 by a perennial form. Statistical analysis on each single score showed a positive relevance ( P < 0.001) from baseline to all other visits. No local or systemic complications were recorded. Conclusions: Tacrolimus has been proposed as a treatment for severe forms of VKC. This study has confirmed the safety and efficacy of tacrolimus 0.1% eye drops in a large pediatric population of patients affected by a severe form of VKC who responded poorly to cyclosporine eye drops.